Elements of education 4.0 as support for promoting education 5.0 in technological higher education institutions - Rego, Emilia Augusta (2026)
The rapid advancement of digital technologies is accelerating educational transformation worldwide while also deepening disparities in developing countries, where infrastructure and educator training remain uneven. This context reinforces the transition from Education 4.0, which emphasizes digitalization and automation, toward Education 5.0, characterized by human-centered, AI-supported, and sustainability-oriented learning ecosystems. In Brazil, Technological Higher Education Institutions (THEIs) continue to face persistent barriers to this transition, including limited Information and Communication Technology (ICT) resources, insufficient digital readiness, and unequal access to emerging technologies. The objective of this research is to identify and characterize the main elements of current Education 4.0 frameworks that could facilitate the adoption of Education 5.0 in Brazilian THEIs. This study adopts a qualitative, exploratory-descriptive design, developed through a Systematic Literature Review (SLR) that analyzed five consolidated Education 4.0 frameworks, followed by validation by three experts. The empirical phase included 54 PhD professors and researchers from 32 federal, state, private, and community THEIs across 14 Brazilian states. Data were collected through structured questionnaires combining Likert-type evaluation and open-ended questions, enabling refinement of the proposed elements. The results validate three dimensions—Technology, Skills, and Innovation—comprising a total of 35 elements identified, refined, and approved by the expert committee. The Technology dimension includes 13 elements, with highly rated components such as Responsible and Sustainable Tech Training, AI Literacy and Computational Thinking, Smart Infrastructure for Adaptive and Technology-Enhanced Learning, High-Speed Networks, and AI-Enhanced Ecosystems. The Skills dimension consists of 10 elements, emphasizing Analytical and Critical Thinking, Socioemotional Competencies, Cognitive and Socioemotional Skills for 21st-Century Professionals, Integration of Human and Technical Skills, and Complex Problem-Solving. The Innovation dimension contains 12 elements, highlighting Reflective and Collaborative Teaching, Inclusion, Sustainability and Societal Impact, Problem-Based and Scenario-Based Learning, Technology-Enhanced Learning Analytics, and Neuroscience. In conclusion, the three validated dimensions and 35 elements constitute a foundational theoretical structure to support the evolution of Education 5.0 in Technological Higher Education Institutions in Brazil. As a contribution to academia, this study advances the literature by consolidating, organizing, and validating key elements from Education 4.0 frameworks into a structured and empirically supported set of elements aligned with Education 5.0 principles. As a contribution to practitioners and society, the findings provide evidence-based guidance for institutional leaders and educators to strengthen digital transformation strategies, improve teacher development, and promote more equitable, ethical, and sustainable learning environments.